Health literacy and preventive behaviors toward microplastic contamination among communities in the major river basins of northeastern Thailand - Santisith Khiewkhern; Supatra Noo-In; Chitkamon Srichomphoo; Jirarat Ruetrakul; Ruchakron Kongmant; Nitikorn Phoosuwan (PLoS ONE, 2026)
Background Microplastic contamination in freshwater systems poses increasing environmental and public health risks, particularly for riverine communities. Health literacy may critically influence individuals’ capacity to recognize exposure pathways and adopt preventive behaviors. Objective This study assessed health literacy and preventive behaviors related to microplastic contamination and examined factors associated with poor health literacy and preventive practices among communities in northeastern Thailand. Methods A cross-sectional survey was conducted among 942 adults residing along the Mekong, Chi, and Mun River basins. Health literacy and preventive behaviors were assessed using a structured questionnaire. Multivariable logistic regression was performed to identify associated factors, whilst adjusted odds ratios (aOR) with 95% confidence intervals (CI) and statistical significance set at p < 0.05. Results Nearly half of the participants exhibited insufficient health literacy, with decision-making identified as the weakest domain. While approximately half reported good preventive behaviors, insufficient health literacy was the strongest determinant of poor preventive practices (aOR=9.18; 95%CI: 6.62–12.72). Residents of rural (aOR=6.47; 95%CI: 4.47–9.37) and semi-urban (aOR=2.45; 95%CI: 1.76–3.41) communities and younger age groups were significantly more likely to have poor health literacy. Community type (semi-urban: aOR=2.61; 95%CI: 1.81–3.78) and longer duration of residence (>60 years: aOR=2.36; 95%CI: 1.37–4.06) were also significantly associated with preventive behaviors. Conclusion Health literacy is a critical determinant of microplastic-related preventive behaviors. Interventions targeting higher-order literacy skills, particularly decision-making, should be integrated into environmental health and public health strategies to reduce microplastic exposure and promote sustainable preventive practices in riverine communities .